Efektifitas Penanganan Komplain Melalui Aplikasi PLN Mobile Untuk Mendukung Kinerja Pelayanan Dan Kepuasan Pelanggan Di PT PLN ULP Balikpapan Utara - Alyanas Alyanas (CV. ITTC INDONESIA, 2024)
Service performance and customer satisfaction are important factors in a public service. This is certainly when service performance can be maximized and customer satisfaction is also fulfilled will provide a positive assessment. One factor that can improve this is the PLN Mobile application. This application can be used online anywhere and anytime so that the service becomes more optimal. The formulation of the problem in this study is (1) how does the effectiveness of complaint handling through the PLN Mobile application affect the service performance of PT PLN (Persero) Balikpapan Utara Customer Service Unit; (2) how does the effectiveness of complaint handling through the PLN Mobile application affect customer satisfaction of PT PLN (Persero) Balikpapan Utara Customer Service Unit; (3) how does service performance affect customer satisfaction of PT PLN (Persero) Balikpapan Utara Customer Service Unit. This study uses a quantitative approach. Data mining using questionnaires. This type of research is explanatory research. The sample of this study was 150 users of PT PLN (Persero) North Balikpapan Customer Service Unit who had filed complaints through the PLN mobile application. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS software version 4. The results of this study are (1) There is an influence of the effectiveness of complaint handling through the PLN Mobile application on the service performance of PT PLN (Persero) Balikpapan Utara Customer Service Unit, this is based on the P-Values value of 0.049 < 0.05 and the positive T-Statistics value (1.986) > 1.96. (2) There is an influence of the effectiveness of complaint handling through the PLN Mobile application on customer satisfaction of PT PLN (Persero) Balikpapan Utara Customer Service Unit, this is based on the P-Values value of 0.000 < 0.05 plus the positive T-Statistics value (6.307) > 1.96). (3) There is an influence of service performance on customer satisfaction at PT PLN (Persero) North Balikpapan Customer Service Unit. This is based on the P-Values of 0.002 < 0.05 and positive T-Statistics values (3.044) > 1.96.